2008
DOI: 10.1055/s-0028-1087187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fructose and/or Fat in the Diet on Developing the Type 2 Diabetic-like Syndrome in CD-1 Mice

Abstract: The aim of the present study was to examine the interactions of fructose and fat on glucose regulation and lipid metabolism in CD-1 mice. Mice were assigned in five groups. The control group was provided with tap water and a gavage of vehicle; four experimental groups were treated with 150 g/l fructose solution (FS1), fat emulsion (FE), 150 g/l fructose solution and fat emulsion (FS1+FE), or 70 g/l fructose solution and fat emulsion (FS2+FE) for 12 weeks. At the end of the 8th week, both oral glucose tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Emerging evidence shows that excess consumption of fructose rather than glucose and sucrose may result in severe metabolic syndromes in the liver, including IR, NAFLD, hyperlipidemia, hyperuricemia, high plasma FFAs, and even liver inflammation . In addition, high‐fructose/sucrose and high‐fat diets can synergistically induce adverse effects toward animal and human health , predicting an interaction between sugar and fat. After comparing the differences between the previous study and the fructose‐induced in vivo studies, we speculated that the levels of fructose and the presence of FFAs might play key roles in affecting liver cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence shows that excess consumption of fructose rather than glucose and sucrose may result in severe metabolic syndromes in the liver, including IR, NAFLD, hyperlipidemia, hyperuricemia, high plasma FFAs, and even liver inflammation . In addition, high‐fructose/sucrose and high‐fat diets can synergistically induce adverse effects toward animal and human health , predicting an interaction between sugar and fat. After comparing the differences between the previous study and the fructose‐induced in vivo studies, we speculated that the levels of fructose and the presence of FFAs might play key roles in affecting liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…From the data of USDA, aside from sugars, daily fat intake has also sharply increased by about 55% from 1986 to 2007 . Emerging evidence indicates that high‐fat diet would induce metabolic disorders with high‐fructose diet , leading to hyperlipidemia and numerous liver lesions, including NAFLD, IR, uric acid (UA) overproduction, and liver inflammation . Moreover, a previous study showed that fat could induce a faster onset of metabolic symptoms with fructose than sucrose, whereas glucose would not .…”
Section: Introductionmentioning
confidence: 99%
“…35,36 This supports the usefulness of the fructose diet to produce a model for the experimental syndrome of insulin resistance, a precursor condition to type 2 diabetes. Clinical and basic studies have shown that Ang AT1 blockade improves β-cell function, glucose tolerance, and delays the onset of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 53%
“…Increasing ingestion of high calorie food was considered to be a major risk factor of insulin resistance and type 2 diabetes. Zhang et al () observed that HFFD can successfully induce IGR, hyperglycemia, hyperlipidemia, impaired antioxidant potential, and liver steatosis in ICR mice.…”
Section: Discussionmentioning
confidence: 99%